2019
DOI: 10.1504/ijbir.2019.10017790
|View full text |Cite
|
Sign up to set email alerts
|

Developing a measurement for strategic entrepreneurship by linking its dimensions to competitiveness in knowledge-based firms

Abstract: Although there are various definitions of strategic entrepreneurship and there is consensus about its importance, most researchers do not take into account the unique characteristics of this construct. The aim of this study was to develop a strategic entrepreneurship questionnaire and investigate how the dimensions of this measuring tool relate to the competitiveness of knowledge-based firms. The questionnaire was developed in four phases: a literature review, use of existing questionnaires to prepare the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…They identified five dimensions as 'opportunity-based mindset', 'continuous innovation', 'risk-taking', 'value creation' and 'proactive behaviour'. The finding of Siadat and Naeiji (2019) demonstrated that these five dimensions had positive effects on knowledge-based firms' competitiveness. Siddiqui and Jan (2019) developed a framework to evaluate female entrepreneurship's strategic entrepreneurship in the Indian context.…”
Section: Literature Reviewmentioning
confidence: 94%
See 2 more Smart Citations
“…They identified five dimensions as 'opportunity-based mindset', 'continuous innovation', 'risk-taking', 'value creation' and 'proactive behaviour'. The finding of Siadat and Naeiji (2019) demonstrated that these five dimensions had positive effects on knowledge-based firms' competitiveness. Siddiqui and Jan (2019) developed a framework to evaluate female entrepreneurship's strategic entrepreneurship in the Indian context.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Some significant studies related to strategic entrepreneurship are mentioned here. Siadat and Naeiji (2019) identified the major dimensions and factors of strategic entrepreneurship and examined these dimensions using factor analysis. They identified five dimensions as 'opportunity-based mindset', 'continuous innovation', 'risk-taking', 'value creation' and 'proactive behaviour'.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the pertinent research on SE includes work by Siadat and Naeiji [9], who identified the key components and dimensions of SE and used factor analysis to examine its characteristics. Their findings demonstrated that the competitiveness of knowledge-based organisations is positively impacted by the opportunity-based attitude, proactive behaviour, risk-taking behaviour, and constant innovation and value creation.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…SE has garnered increasing scholarly interest in recent years due to its practical importance, and study on the notion of SE has increased greatly since its origin, resulting in a vast research and literature domain [8]. Many researchers emphasise the identification of the growth prospects in SE [9,10]. SE is receiving attention because it supports firms to innovate in terms of employees' abilities and skill development and creating innovative ventures [11].…”
Section: Introductionmentioning
confidence: 99%